Improving Social Justice: A Comprehensive Evaluation of the KPM Assistance Program in Poverty Reduction - Rupiarsieh, Rupiarsieh; Wulandari, Septi; Wulandari, Tri Setya (PERSPEKTIF, 2025)
This study evaluates the effectiveness of the Keluarga Penerima Manfaat (KPM) social assistance program in alleviating poverty in Sumengko Village, Kalitidu District, Bojonegoro Regency, in 2023. A qualitative descriptive method was employed, with data collected through interviews, observations, and documentation involving six respondents. The evaluation utilized William N. Dunn's framework, focusing on effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy, to ensure credible conclusions. The findings indicate that while the program effectively addresses basic needs by distributing 10 kg of rice per household, limitations in rice availability hinder its adequacy and equity. Uneven socialization and misallocation to ineligible households also impact program accuracy. These findings provide a basis for comparing similar programs in other rural settings and highlight the need for improved coordination and oversight. Beyond poverty alleviation, the program has potential broader impacts on community health and education by enhancing food security and reducing economic stress. This comprehensive evaluation emphasizes the importance of addressing logistical and social challenges to optimize the benefits of social assistance programs.